ANALISIS PENGARUH VARIASI PRODUK, CITA RASA, DAN HIGIENITAS TERHADAP MINAT BELI KONSUMEN ( STUDI KASUS PADA ICE CREAM ZANGRANDI SURABAYA) - Saputra, Vony; Mulyati, Awin; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2015)
In this study, the authors examined the extent to which the influence of Product Variations, Taste, and Hygiene to Buy Consumer Interests. A sample of 100 respondents who bought Ice Cream Zangrandi. Sampling using nonrandom collection, the data was processed using SPSS for Windows 17:00 The results of the study conclude that the independent variable most dominant influence on the dependent variable is the taste (0.542), followed by the variable product variations (0.418), and the latter is variable hygiene (0.057). The coefficient of determination (adjusted R2) of 0.889, which means variations in rise and fall of consumer buying interest on ice cream Zangrandi (Y), able to be explained by changes in the variable variation of the product (X1), taste (X2), and hygiene (X3) together of 88.9% and the remaining 11.1% is influenced by other variables that are not discussed in study. Keywords: Product Variations, Taste, hygiene and Buy Consumer Interests.